A Rice Mutant Defective in Si Uptake - Ma, Jian Feng (American Society of Plant Biologists, 2002)
Rice (Oryza sativa) accumulates silicon (Si) in the tops to levels up to 10.0% of shoot dry weight, but the mechanism responsible for high Si uptake by rice roots is not understood. We isolated a rice mutant (GR1) that is defective in active Si uptake by screening M(2) seeds (64,000) of rice cv Oochikara that were treated with 10(−3) m sodium azide for 6 h at 25(o)C. There were no phenotypic differences between wild type (WT) and GR1 except that the leaf blade of GR1 remained droopy when Si was supplied. Uptake experiments showed that Si uptake by GR1 was significantly lower than that by WT at both low and high Si concentrations. However, there was no difference in the uptake of other nutrients such as phosphorus and potassium. Si concentration in the xylem sap of WT was 33-fold that of the external solution, but that of GR1 was 3-fold higher than the external solution at 0.15 mm Si. Si uptake by WT was inhibited by metabolic inhibitors including NaCN and 2,4-dinitrophenol and by low temperature, whereas Si uptake by GR1 was not inhibited by these agents. These results suggest that an active transport system for Si uptake is disrupted in GR1. Analysis of F(2) populations between GR1 and WT showed that roots with high Si uptake and roots with low Si uptake segregated at a 3:1 ratio, suggesting that GR1 is a recessive mutant of Si uptake.